Consumers' perceptions of food ethics in luxury dining. Issue 5 (31st July 2021) - Batat, Wided
Abstract : Purpose: This paper aims to draw on the sociocultural dimensions of food luxury consumption as a new theoretical foundation to explore the consumers' perceptions of ethical food production and consumption practices within luxury gastronomic restaurants. Design/methodology/approach: The authors conducted a contextualized, qualitative exploration of French luxury dining settings among 35 consumers with different profiles, food cultural backgrounds and gastronomic knowledge. Drawing on Thompson's analysis framework, the authors captured the narratives beyond the stories told by participants that describe their perceptions and the meanings they assign to ethical food practices in Michelin-starred restaurants. Findings: The results illustrate how consumers with different profiles perceive ethical food practices within luxury restaurants. The authors identified three segments: novice, advanced and confirmed according to participants' acquaintance with luxury gastronomy codes and values. These three profiles served as a framework to examine consumers' perceptions of ethical food forms – environmental sustainability, food well-being and cultural heritage – within the luxury dining setting. Research limitations/implications: The study revealed no one dominant form of ethical food practices as emphasized in prior studies. Rather, there are multiple forms, including functional, hedonic and symbolic values, related to the degree of familiarity and knowledge of consumers in terms of their luxury gastronomic experiences. The findings show that the perception of ethical food practices within luxury restaurants can encompass additional dimensions such as food well-being and cultural preservation and transmission. This information can enrich the restaurant sustainability literature that principally focuses on health, community and the ecological aspects of food ethics in restaurants. Although this study suggests numerous new insights, there are limitations related to focusing on the French food culture. However, these limitations can help us develop other opportunities for future research. Practical implications: The findings of this study provide luxury professionals and marketers with key insights into effective strategies to integrate sustainable practices while enhancing the luxury experience. The findings show that to encourage luxury businesses and restaurants to promote sustainable practices, it is necessary to enhance the functional, social, emotional and cultural dimensions of the perceived benefits of offering sustainable luxury experiences and reducing the constraints related to sustainability. Social implications: With its focus on the luxury dining settings underpinning the ethical food practices from the perspective of consumers, this research offers novel insights for researchers and luxury professionals interested in ethical and sustainable business practices. Originality/value: This research suggests a new way to study sustainability and ethical food production and consumption practices in luxury dining settings – namely, as multiple, culturally embedded perceptions related to three main profiles of luxury gastronomy consumers: novice, advanced and confirmed.